Stratification of the Risk of Sudden Death in Nonischemic Heart Failure - Pimentel,Maurício (2014)
Despite significant therapeutic advancements, heart failure remains a highly prevalent clinical condition associated with significant morbidity and mortality. In 30%-40% patients, the etiology of heart failure is nonischemic. The implantable cardioverter-defibrillator (ICD) is capable of preventing sudden death and decreasing total mortality in patients with nonischemic heart failure. However, a significant number of patients receiving ICD do not receive any kind of therapy during follow-up. Moreover, considering the situation in Brazil and several other countries, ICD cannot be implanted in all patients with nonischemic heart failure. Therefore, there is an urgent need to identify patients at an increased risk of sudden death because these would benefit more than patients at a lower risk, despite the presence of heart failure in both risk groups. In this study, the authors review the primary available methods for the stratification of the risk of sudden death in patients with nonischemic heart failure.